Are the marginal convergence outcomes of the Cohesion Policy diminishing? - Butkus, Mindaugas; Mačiulytė-Šniukienė, Alma; Matuzevičiūtė, Kristina (Journal of Business Economics and Management, 2020)
Significant disparities still exist between regions of the European Union, even though substantial Cohesion investments are directed to address this issue. To adjust the Cohesion Policy (CP), researchers assess the returns of the CP, but almost all studies are carried out at NUTS1&2 or a country level, even though significant disparities occur at NUTS3 level. Moreover, just a few studies examine the non-linear effects of the CP, and none of them covers the NUTS3 disaggregation level. Filling the gap of previous contributions, the paper aims to investigate convergence outcomes of the CP at NUTS2&3 level and to identify whether the marginal effect of the CP is diminishing. The estimation strategy is based on the modified specification of the difference-in-differences estimator that has an advantage while examining policy effects, using non-experimental data. Based on research findings, the essential guidelines for the improvement of the CP can be drawn up: i) the distribution policy of Cohesion investments should focus on smaller territorial units to reduce disparities at NUTS3 level; ii) the intensity of the CP’s transfers has to be optimised because excessive intensity does not provide a positive return.